EXPERIENCE OF USING REXETIN IN PATIENTS WITH PSORIATIC DISEASE (ResearchJet Journal of Analysis and Inventions, 2021)
In our study, we used the drug Rexetin in the complex treatment of psoriasis in our work, we treated 28 patients with a diagnosis of vulgar psoriasis. 16 men and 12 women aged 17 to 65 years. The duration of the disease varied from 6 months to 14 years. As a result of our work, the following conclusions were made: traditional treatment of psoriasis with the use of a modern antidepressant-Rexetin led to a faster cure of patients, which may serve as a prospect for the active use of this drug in practical health care.